Employment regimes and the quality of work (New York, 2009)
"The book makes a major new contribution to the sociology of employment by comparing the quality of working life in European societies with very different institutional systems - France, Germany, Great Britain, Spain and Sweden. It focuses in particular on skills and skill development, opportunities for training, the scope for initiative in work, the difficulty of combining work and family life and the security of employment.